2015
DOI: 10.1111/wvn.12080
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Practice Beliefs and Implementation Before and After an Initiative to Promote Evidence‐Based Nursing in an Ambulatory Oncology Setting

Abstract: Background: The purpose of evidence-based practice (EBP) in nursing is to improve patient outcomes, providing the best and most up-to-date care practices. In 2011, a nurse-led committee convened to develop an institute-wide initiative to promote EBP with oncology nurses at the Dana-Farber Cancer Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
(28 reference statements)
5
37
1
4
Order By: Relevance
“…This study findings also support the practical benefits of the partnership among academia and other institutions, in which expertise and resources are pooled to facilitate EBP adoption across multiple institutions in the region (Gawlinski & Becker, 2012;Granger et al, 2012;Weeks et al, 2011). Similar study findings were previously reported from an educational program in which EBP beliefs and EBP implementation were improved (Abdullah et al, 2014;Levin, Fineout-Overholt, Melnyk, Barnes, & Vetter, 2011), although another EBP educational program based on the ARCC model showed no statistically significant improvements in EBP beliefs and EBP implementation (Underhill, Roper, Siefert, Boucher, & Berry, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…This study findings also support the practical benefits of the partnership among academia and other institutions, in which expertise and resources are pooled to facilitate EBP adoption across multiple institutions in the region (Gawlinski & Becker, 2012;Granger et al, 2012;Weeks et al, 2011). Similar study findings were previously reported from an educational program in which EBP beliefs and EBP implementation were improved (Abdullah et al, 2014;Levin, Fineout-Overholt, Melnyk, Barnes, & Vetter, 2011), although another EBP educational program based on the ARCC model showed no statistically significant improvements in EBP beliefs and EBP implementation (Underhill, Roper, Siefert, Boucher, & Berry, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…3. Este grupo aborda temáticas referentes a las posibilidades de práctica avanzada en grupos específicos (30)(31)(32)(33)(34)(35)(36); el resultado de estar formado en un grupo interprofesional PS (36); la pertinencia de integrar las TIC (33) a la práctica avanzada; el ejercicio y la percepción de las prácticas avanzadas en campos clínicos específicos (29,34,37,38) y los retos de la práctica avanzada (35,39,40).…”
Section: Resultsunclassified
“…Esta formación avanzada permitirá el descubrimiento de nuevos roles, como el de empresario, que contrastan con los hasta ahora descritos (3), y fortalecerá prácticas requeridas por las poblaciones más vulnerables como los niños maltratados (34), los enfermos crónicos, en especial aquellos que son atendidos por sus familias y requieren modelos innovadores de apoyo para sus situaciones específicas (38,42).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[36] Mentorship and continuing education are often pointed to as successful strategies. [34,40] In our study, the facilitators trained together in literature searching, analysing scientific articles, the EBP implementation process, and the facilitator role. Throughout the project, they were expected to stimulate and increase the nurses' interest, awareness, and engagement in EBP, and to discuss EBP in daily caring situations.…”
Section: Discussionmentioning
confidence: 99%